Randomized clinical trial comparing helmet continuous positive airway pressure (hCPAP) to facemask continuous positive airway pressure (fCPAP) for the treatment of acute respiratory failure in the emergency department - Adi, Osman; Via, Gabriele; Salleh, Siti Hafsah; Tan, Wan Chuan; Ab Rahman, Jamalludin; Nik Muhammad, Nik Azlan; Atan, Rafidah; Yunos, Nor'Azim (Elsevier Inc., 2021)
Study objective: To determine whether non-invasive ventilation (NIV) delivered by helmet continuous positive airway pressure (hCPAP) is non-inferior to facemask continuous positive airway pressure (fCPAP) in patients with acute respiratory failure in the emergency department (ED). Methods: Non-inferiority randomized, clinical trial involving patients presenting with acute respiratory failure conducted in the ED of a local hospital. Participants were randomly allocated to receive either hCPAP or fCPAP as per the trial protocol. The primary endpoint was respiratory rate reduction. Secondary endpoints included discomfort, improvement inDyspnea and Likert scales, heart rate reduction, arterial blood oxygenation, partial pressure of carbon dioxide (PaCO2), dryness of mucosa and intubation rate. Results: 224 patients were included and randomized (113 patients to hCPAP, 111 to fCPAP). Both techniques reduced respiratory rate (hCPAP: from33.56±3.07 to 25.43±3.11 bpmand fCPAP: from33.46±3.35 to 27.01± 3.19 bpm), heart rate (hCPAP: from 114.76 ± 15.5 to 96.17 ± 16.50 bpm and fCPAP: from 115.07 ± 14.13 to 101.19 ± 16.92 bpm), and improved dyspnea measured by both the Visual Analogue Scale (hCPAP: from 16.36 ± 12.13 to 83.72 ± 12.91 and fCPAP: from 16.01 ± 11.76 to 76.62 ± 13.91) and the Likert scale. Both CPAP techniques improved arterial oxygenation (PaO2 from 67.72 ± 8.06 mmHg to 166.38 ± 30.17 mmHg in hCPAP and 68.99±7.68mmHg to 184.49±36.38mmHg in fCPAP) and the PaO2:FiO2 (Partial pressure of arterial oxygen: Fraction of inspired oxygen) ratio from 113.6 ± 13.4 to 273.4 ± 49.5 in hCPAP and 115.0 ± 12.9 to 307.7±60.9 in fCPAP. The intubation ratewas lowerwith hCPAP (4.4% for hCPAP versus 18% for fCPAP, absolute difference −13.6%, p = 0.003). Discomfort and dryness of mucosa were also lower with hCPAP.